2011
DOI: 10.1111/j.1365-2869.2011.00931.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotyping interindividual variability in obstructive sleep apnoea response to temazepam using ventilatory chemoreflexes during wakefulness

Abstract: SUMMARY Centrally active agents have a variable impact in patients with obstructive sleep apnoea (OSA) that is unexplained. How to phenotype the individual OSA response is clinically important, as it may help to identify who will be at risk of respiratory depression and who will benefit from a centrally active agent. Based on loop gain theory, we hypothesized that OSA patients with higher central chemosensitivity have higher breathing instability following the use of a hypnosedative, temazepam. In 20 men with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 34 publications
3
29
1
Order By: Relevance
“…[41][42][43][44][45][46][47] In preselecting patients with OSA with low respiratory arousal thresholds, we anticipated that trazodone would reduce apnea severity similar to recent findings with eszopiclone whereby eight patients with OSA and a low arousal threshold had invariable reductions in their AHI. 9 There are several possibilities that may account for the apparent disparity between studies, outlined in the next paragraphs.…”
Section: Mechanistic Insight Into the Effects Of Trazodone On Sleep Amentioning
confidence: 76%
“…[41][42][43][44][45][46][47] In preselecting patients with OSA with low respiratory arousal thresholds, we anticipated that trazodone would reduce apnea severity similar to recent findings with eszopiclone whereby eight patients with OSA and a low arousal threshold had invariable reductions in their AHI. 9 There are several possibilities that may account for the apparent disparity between studies, outlined in the next paragraphs.…”
Section: Mechanistic Insight Into the Effects Of Trazodone On Sleep Amentioning
confidence: 76%
“…We (Wang et al, 2011) and others (Eckert et al, 2011;Edwards et al, 2012) have identified certain respiratory phenotypes that may characterise sub-groups of OSA patients that will improve sleep apnea following use of CNS depressants. In these patients, the use of safe doses of a respiratory depressant may modulate the chemoreflexes by alteration of the VRT or/and chemical drives/loop gain.…”
Section: Discussionmentioning
confidence: 99%
“…OSA has been characterized with high loop gain/chemical drive/chemosensitivity which can cause ventilatory over-shoot, and the repetitive pattern is crucial in precipitating a cyclic sleep-disordered breathing pattern (White, 2005;Dempsey et al, 2010). In our OSA patients, the mild dose of morphine may reduce ventilatory chemosensitivity, and therefore the controller gain and the chance of cyclic ventilatory overshoot, thus improve OSA (Edwards et al, 2012;Wang et al, 2011). On the other hand, the increased VRT in our OSA patients may indicate an increased RRT and a widened CO 2 reserve, and a greater breathing stability during sleep.…”
Section: Morphine Effect On Breathing Stability During Sleepmentioning
confidence: 96%
See 1 more Smart Citation
“…To date, the effects of sedatives on either the ArTH, OSA severity, or both have been assessed in a few studies involving relatively small numbers of participants (12,14,(31)(32)(33)(34). The ArTH consistently increases (becomes more negative) with sedatives, although the effects on AHI have been inconsistent.…”
Section: Discussionmentioning
confidence: 99%